2012
DOI: 10.1039/c2gc35982k
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid derived renewable polyamides via thiol–ene additions

Abstract: The syntheses of new fatty acid-derived amine functional monomers via the thiol-ene addition reaction as well as the thereof derived renewable polyamides were investigated. The thiol-ene addition of cysteamine hydrochloride to the double bonds of methyl 10-undecenoate, methyl oleate, and methyl erucate yielded heterodifunctional monomers in good yields. The thus obtained monomers were homopolymerized, copolymerized with each other as well as copolymerized with adipic acid and 1,6-hexamethylene diamine to yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 28 publications
2
48
0
1
Order By: Relevance
“…Next, ester 1 was treated with 1,1′-azobis(cyclohexanecarbonitrile) (ABCN) and 2-mercaptoethylamine hydrochloride in dioxane/ethanol 70:30 (v:v) to obtain methyl 11-(2-aminoethylthio)undecanoate ( 2 ) in 89% yield. The structures of compounds 1 and 2 were in agreement with the reported literature data [1415]. …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Next, ester 1 was treated with 1,1′-azobis(cyclohexanecarbonitrile) (ABCN) and 2-mercaptoethylamine hydrochloride in dioxane/ethanol 70:30 (v:v) to obtain methyl 11-(2-aminoethylthio)undecanoate ( 2 ) in 89% yield. The structures of compounds 1 and 2 were in agreement with the reported literature data [1415]. …”
Section: Resultssupporting
confidence: 89%
“…This crude product mixture was concentrated and purified by column chromatography with hexane/ethyl acetate (92:8, v/v) to obtain pure methyl 11-(2-aminoethylthio)undecanoate ( 2 ) in 89% yield (7.41 g). The purified product was characterized by 1 H and 13 C NMR, IR and ESIMS spectral studies and the structure was confirmed by comparing the data with those reported in the literature [15]. …”
Section: Methodsmentioning
confidence: 94%
“…Dimer fatty acid-based polyamides are a special class of biopolymers derived from plant oils [1,18,19]. Compared to other polyamides, they feature lower water uptake and ease of processing (owing to a lower melt viscosity).…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy for derivatization of unsaturated fatty acid methyl esters was direct synthesis of keto-fatty acid esters by Wacker oxidations employing oxygen as a sole re-oxidant and amine functionalization of the thus obtained keto-fatty acid esters by reductive amination [41]. In another work, unsaturated bond of fatty acid-derived methyl 10-undecenoate, methyl oleate, and methyl erucate was utilized in the thiol-ene addition reaction of cysteamine hydrochloride to obtain amine functional branched monomers [42]. Monomers were further used to obtain homo and copolymers with adjustable thermal and solubility properties.…”
Section: Synthesis Of Biopolyamides From Other Bio-based Monomersmentioning
confidence: 99%